Enhancing Employee Performance Using Workgroup Effectiveness: Role of Member Trust - Wanuri; Khayatun, Siti; Hartarini, Yovita Mumpuni (Management Analysis Journal, 2024)
Research  aims  to  offer  comprehensive  understanding  of  the  factors  influencing organizational performance, particularly in the context of member trust, thereby contributing to broader discourse on human capital management and cooperative development.  Utilizing  multidimensional  framework  of  human  capital  and grounded  in  prevailing  challenges  faced  by  cooperative  businesses,  research elucidates pivotal role of human capital as organizational performance. Approach research was based on descriptive research techniques, in cross-sectional survey, is to observe (collect data about) specific occurrence, often at single point in time. To address research questions, this study adopts descriptive research technique and survey measures to capture objective and social reality of employee performance. Sample  included  140  respondents  of  Flower  Market  Traders  Association  in Kopeng, Semarang district, Central Java Province. Data gathering period lasted from January until October 2023. Researcher created questionnaire and collected data using Google Forms. Data analysis was conducted using Structural Equation Modeling  (SEM)  with  Smart-PLS  (Partial  Least  Square)  software.  Based  on study's results, workgroup effectiveness directly influences employee performance and contributes to its success. Moreover, member trust as moderator in correlation between  workgroup  effectiveness  and  employee  performance.  Research  offers theoretical and practical implications for implementing workgroup effectiveness to enhance employee performance and member trust as moderator.